Successful Management of Hypertriglyceridemia‐Induced Acute Pancreatitis in Resource‐Limited Setting: A Case Report and Brief Review of the Literature - Mukti Nath Sankhi; Sabin Rajbhandari; Ayush Rayamajhi; Pramila Dhakal; Nabin Adhikari; Santosh Kumar Singh (Clinical Case Reports, 2026)
ABSTRACT A 44‐year‐old man presented with acute abdominal pain and was diagnosed with hypertriglyceridemia‐induced acute pancreatitis. He was managed with fluid resuscitation, analgesia, and insulin infusion and had good recovery. Recognizing hypertriglyceridemia as an etiology of acute pancreatitis and insulin infusion as a treatment modality is important in a resource‐limited setting.